Pomegranate (Punica granatum): a functional superfruit with therapeutic properties (Agroindustrial Science, 2020)
The Pomegranate (Punica granatum) is a fruit that contains innumerable chemical compounds with a high biological value distributed in the bark, carpel membranes, juice (arils) and seeds. The Pomegranate known as a super fruit because of its proven antioxidant power and its health benefits that help slow down the aging process, maintain healthy skin, reduce blood pressure thus fighting heart disease, promote blood circulation, and prevents some types of cancer. The pomegranate has a high content of calcium, magnesium, potassium, and phosphorus (0.01%, 0.012%, 0.236%, and 0.036% respectively), which are part of various enzymes that help prevent alterations in the metabolism of fats and carbohydrates. The purpose of this work was to compile the various investigations on the therapeutic properties of the compounds of the pomegranate.